Rhapsody as the leading genre modus of George Gershwin’s concert music - Antonova, Olena (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the study. George Gershwin’s creative legacy includes four works that, by their instrumentation — piano solo and orchestra — belong to the instrumental concerto genre. However, only one is explicitly titled “concerto”, another is labeled “variations”, and two are designated as “rhapsodies”. The selection of “rhapsody” as a primary genre title actualizes the appeal to these works in order to understand the composer’s vision of the nature of the concert genre. Additionally, the disparity in the popularity and scholarly exploration of his two rhapsodies necessitates a focus on the second one. The main objective of the study is to reveal the specifics of the leading genre modus in George Gershwin’s concert music, using his Second Rhapsody as a case study. The methodology includes the following methods: cultural analysis to contextualize the emergence of the Second Rhapsody; comparative analysis to identify similarities and differences between the Second Rhapsody and Rhapsody in Blue; structural-functional, genre, and intonationaldramaturgical analyses to perform a comprehensive examination of the works; theoretical generalization to draw conclusions. The main results and conclusions. The Second Rhapsody for piano and orchestra by George Gershwin (1931) is considered. The circumstances of its creation, the connection with the Hollywood film Delishious by David Butler and the commission of the Boston Symphony Orchestra conductor Serge Koussevitzky are described. Parallels are drawn between the Second Rhapsody and Rhapsody in Blue in terms of their figurative content, compositional and dramaturgical organization, thematic development, nature of interaction between instrumental parts. The choice of the genre name for these works is discussed, considering external influences and Gershwin’s deliberate orientation to Franz Liszt’s tradition. The forms of Gershwin’s rhapsodies, their thematic content and dramaturgical accents are analyzed. Improvisation plays a pivotal role, reflected both in deviations from standard compositional norms and in the relatively free presentation of material. Despite this freedom, strong intonational connections underpin the unity of the Second Rhapsody. These connections extend beyond thematic elements to encompass textural backgrounds and figurative passages. The study compares the quantitative and qualitative composition of solo episodes in both rhapsodies, emphasizing how Gershwin’s pianistic style influenced their presentation. Examples illustrate the constructive basis of their textural organization. The differences between the rhapsodies in the ratio of solo and orchestral episodes are considered. The manifestations of the play principle are characterized. The conclusion is made about the dual-genre nature of Gershwin’s rhapsodies, blending features of the rhapsody genre and the concerto genre. The originality of this synthesis lies in the composer’s nuanced interpretation of both genres: prioritizing improvisation in the rhapsody and the principle of play in the concerto. Finally, it is noted that the Second Rhapsody reflects a marked advancement in Gershwin’s compositional technique. Compared to Rhapsody in Blue, the Second Rhapsody demonstrates greater formal cohesion, more organic interaction between soloist and orchestra, and increased complexity and individuality in its musical language